368 Markers for Invasive Bacterial Infection in Well-Appearing Young Febrile Infants. The Value of Procalcitonin. (October 2012) - Mintegi, S; Bressan, S; Gomez, B; Dalt, L Da; Blázquez, D; Olaciregui, I; Torre, M De La; Palacios, M; Berlese, P; Ruano, A
Abstract : Background: In the last decade, the procalcitonin (PCT) has been introduced in many protocols for the management of the febrile child. However, its value among young well-appearing infants is not completely defined. Objective: To assess the value of PCT in diagnosing serious bacterial infections and specifically invasive bacterial infections (IBIs) in well-appearing infants under 3 months of age with fever without source (FWS). Design and Methods: Retrospective study including well-appearing infants under 3 months of age with FWS attended in seven European Paediatric Emergency Departments. An IBI was defined when a bacterial pathogen was isolated in blood or cerebrospinal fluid culture. Results: A total of 1, 531 infants under 3 months of age with FWS were attended. There were 1, 112 well-appearing infants in whom PCT and a blood culture were performed. Among them, 23 (2.1%) were diagnosed with an IBI. A multivariate analysis showed that, among different epidemicological data and blood tests, PCT was the only independent risk factor for having an IBI (OR 21.69 if PCT 0.5 ng/mL). Comparing with C-Reactive Protein, PCT showed a better performance to rule-in an IBI. Among patients with normal urine dipstick and short-evolution fever (less than 6 hours), areas under the ROC curve were 0.819 and 0.563, respectively for detecting IBIs. Conclusions: Among young infants with FWS, PCT showed a better performance than C-Reactive Protein in identifying patients with IBIs and, mainly in those patients with normal urine dipstick and short-evolution fever, PCT seems to be also the best marker to rule out an IBI.